Synthesis of polyfunctional quinolizidine alkaloids: development towards selective glycosidase inhibitors - Pandey, Ganesh; Grahacharya, Debasish; Shashidhara, K. S.; Khan, Mohammad Islam; Puranik, Vedavati G. (Organic & Biomolecular Chemistry, 2009)
A highly divergent route to a variety of quinolizidine alkaloids is described. The enantiomeric precursors 22a and 22b utilized for the synthesis of these alkaloids were constructed stereospecifically from the PET cyclization of the corresponding acetylene tethered alpha-trimethylsilyl amine moieties 21a and 21b, respectively, both of which were synthesised from D-ribose. The polyhydroxy quinolizidine alkaloid 7 was found to be a selective inhibitor of alpha-galactosidase with Ki 83.9 mu M. The amine analogs 18, 12 and 10 are found to be selective and potent inhibitors of alpha-glucosidase with Ki 28, 120 and 140 mu M, respectively.